PERSEPSI DAN REVIKTIMISASI PADA PEREMPUAN PENYINTAS KEKERASAN SEKSUAL - Benedicta Herlina Widiastuti (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
Survivors’ prevalence for revictictimization is at stake. Survivors’ perceptions are very important in it. This study aimed to describe and explain those perspectives. Case study is the way taken to capture the particularity of the survivor’s perception. The interview was analyzed by using narrative analysis. The four survivors in this study experienced revictimization by the previous and new perpetrators. The findings showed that the perception of women’s worthiness is bound in men is the key to revictimization. Inability to see that violence is abnormal and inability to put blame on the right person is also crucial. Recommendation for counselors and survivors are discussed